Non-contact respiration monitoring using impulse radio ultrawideband radar in neonates. Issue 6 (5th June 2019) - Kim, Jong Deok; Lee, Won Hyuk; Lee, Yonggu; Lee, Hyun Ju; Cha, Teahyen; Kim, Seung Hyun; Song, Ki-Min; Lim, Young-Hyo; Cho, Seok Hyun; Cho, Sung Ho; Park, Hyun-Kyung
Abstract : Vital sign monitoring in neonates requires adhesive electrodes, which often damage fragile newborn skin. Because impulse radio ultrawideband (IR-UWB) radar has been reported to recognize chest movement without contact in adult humans, IR-UWB may be used to measure respiratory rates (RRs) in a non-contact fashion. We investigated the feasibility of radar sensors for respiration monitoring in neonates without any respiratory support to compare the accuracy and reliability of radar measurements with those of conventional impedance pneumography measurements. In the neonatal intensive care unit, RRs were measured using radar (RRRd ) and impedance pneumography (RRIP ) simultaneously. The neonatal voluntary movements were measured using the radar sensor and categorized into three levels (low [M0 ], intermediate [M1 ] and high [M2 ]). RRRd highly agreed with RRIP ( r = 0.90; intraclass correlation coefficient [ICC] = 0.846 [0.835–0.856]). For the M0 movement, there was good agreement between RRRd and RRIP (ICC = 0.893; mean bias −0.15 [limits of agreement (LOA) −9.6 to 10.0]). However, the agreement was slightly lower for the M1 (ICC = 0.833; mean bias = 0.95 [LOA −11.4 to 13.3]) and M2 (ICC = 0.749; mean bias = 3.04 [LOA –9.30 to 15.4]) movements than for the M0 movement. In conclusion, IR-UWB radar can provide accurate and reliable estimates of RR in neonates in a non-contact fashion. The performance of radar measurements could be affected by neonate movement.